FluxPRT: An Adaptable and Extensible Proteomics LIMS - Alfaro-Espinoza, Elizabeth Regina; Paiva, Lucas Ferreira; Faria-Campos, Alessandra C.; Baracat-Pereira, Maria Cristina; Campos, Sérgio Vale Aguiar (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2021: Anais do XIV Simpósio Brasileiro de Bioinformática, 2021)
Proteomics is a fundamental research area that focuses on large-scale protein analysis. Data generated from experimental approaches in proteomics is becoming increasingly complex to organize and manage. Laboratory Information Management Systems (LIMS) allow this data to be managed in a flexible and efficient way. However, most LIMS have a high cost and are directed at specific needs. This work introduces FluxPRT, a comprehensive and adaptable proteomics workflow-based LIMS supported by an interactive web page guide aimed at assisting novice researchers in a proteomics lab. FluxPRT is available at http://www.flux2.luar.dcc.ufmg.br and provides an important tool to assist preotemics research.